Cystic Echinococcosis in a Single Tertiary Care Center in Rome, Italy. (14th September 2013) - Petrone, Linda; Cuzzi, Gilda; Colace, Lidia; Ettorre, Giuseppe Maria; Busi-Rizzi, Elisa; Schininà, Vincenzo; Pucillo, Leopoldo; Angeletti, Claudio; Pane, Stefania; Di Caro, Antonino; Bordi, Eugenio; Girardi, Enrico; et al.
Abstract : Background . Cystic echinococcosis (CE) is a chronic, clinically complex, and neglected disease. Its prevalence in Italy, a country of medium to high endemicity, remains poorly defined, as notification has long ceased to be mandatory. Methods . We set up a retrospective cohort study involving all CE patients followed at our institute between January 2005 and December 2012. Demographical and clinical features were recorded and analyzed. Results . CE was found in 28 patients (64.3%), mostly Italians from the central regions (50%), followed by subjects from the islands (33.3%) and Southern Italy (16.7%). Their median age was 45 years (IQR: 38.5–66.5), with Eastern Europeans being significantly younger (28 years, IQR: 19–39) than other patients (P ≤ 0.0001 ). A total of 149 cysts, mostly with hepatic localization (96%), were described. Based on the WHO classification, the cysts were mainly small (80.5%) and active (CE1 (73.8%); CE2 (7.4%)). Active cysts were more common in Eastern Europeans (85.7%) than Italians (66.7%). Conclusion . Our data confirm CE occurrence in Italy. We emphasize the importance to have a national CE registry, opportunely recently introduced. This is essential to assess CE prevalence in this country, implement appropriate control measures, and improve patient management.